Do border policies reduce flows of Venezuelan migrants?. Issue 16 (20th September 2022) - Cuesta, Jose; Chagalj, Cristian
ABSTRACT: Conventional wisdom suggests that migration policy has a significant, unidirectional effect on migration, namely, that tough policies slash inflows, while the reverse is true for permissive policies. We do not find evidence for this in the current Venezuelan migration crisis. In reality, policies shift following large inflows as much as large inflows follow policy shifts. This finding brings into question the efficacy of unilateral and uncoordinated border policies.